What Influences Malaysian Nurses to Participate in Continuing Professional Education Activities? - Mei Chan Chong, RN, MSc, SCM; Kenneth Sellick, RN, PhD, RPN; Karen Francis, RN, PhD, BHSN, DHSN; Khatijah Lim Abdullah, RN, PhD, NICU (Elsevier, 2011)
A cross sectional descriptive study, which involved government hospitals and health clinics from Peninsular Malaysia sought to identify the continuing professional education (CPE) needs and their readiness for E-learning. This paper focuses on the first phase of that study that aimed to determine the factors that influence nurses' participation in CPE. Methods: Multistage cluster sampling was used to recruit 1,000 nurses randomly from 12 hospitals and 24 health clinics from four states in Peninsular Malaysia who agreed to be involved. The respondent rate was 792 (79.2%), of which 562 (80%) had participated in CPE in the last 12 months. Results: Findings suggested that updating knowledge and providing quality care are the most important factors that motivate participation in CPE, with respective means of 4.34 and 4.39. All the mean scores for educational opportunity were less than 3.0. Chi-square tests were used to test the association of demographic data and CPE participation. All demographical data were significantly associated with CPE participation, except marital status. Conclusions: Implementation of mandatory CPE is considered an important measure to increase nurse's participation in CPE. However, effective planning that takes into consideration the learning needs of nurses is recommended.